2021
DOI: 10.1177/10781552211020805
|View full text |Cite
|
Sign up to set email alerts
|

Drug- and patient-related factors are the strongest predictors of endocrine therapy adherence in breast cancer patients

Abstract: Purpose Medication non-adherence to treatment regimens can severely impact the mortality of patients afflicted with breast cancer.The purpose of this study was to identify factors that contribute to non-adherence to endocrine therapy in breast cancer treatment plans. Methods Thirty-two women with a breast cancer diagnosis were surveyed by pharmacists and pharmacy students to identify the patient- related factors (e.g. patient personal beliefs, education level), drug-related factors (e.g. patient drug allergies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Unique to this study was that treatment nonadherence of the parent due to prioritizing the child's treatment was identified as a concern. This is in addition to studies that have found finances and the provider‐patient relationship were associated with non‐adherence 18–20 . Respondents noted that healthcare providers must be aware of this and help the parent adhere to their treatment plan.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Unique to this study was that treatment nonadherence of the parent due to prioritizing the child's treatment was identified as a concern. This is in addition to studies that have found finances and the provider‐patient relationship were associated with non‐adherence 18–20 . Respondents noted that healthcare providers must be aware of this and help the parent adhere to their treatment plan.…”
Section: Discussionmentioning
confidence: 91%
“…This is in addition to studies that have found finances and the provider-patient relationship were associated with nonadherence. [18][19][20] Respondents noted that healthcare providers must be aware of this and help the parent adhere to their treatment plan.…”
Section: Discussionmentioning
confidence: 99%
“…Depression and anxiety were both negatively associated with adherence [ 10 39 52 62 90 91 92 93 94 95 96 97 98 99 ]; however, one study on anxiety suggested a positive relationship between anxiety and adherence [ 95 ]. A family history of breast or ovarian cancer [ 80 100 ], frailty [ 61 ], pain [ 42 46 101 102 ], poor sleep quality [ 103 104 ], smoking/substance use [ 54 66 85 105 106 ], lower cognitive function [ 48 55 61 67 90 94 107 ], concern belief [ 32 46 105 108 109 110 ], strong belief in the risk of recurrence [ 47 ], negative decisional balance [ 111 112 113 ], and poor personal belief [ 114 ] were negatively associated with adherence to AHT. In contrast, better quality of life [ 115 116 117 118 ], positive necessity [ 10 44 97 119 120 121 ], positive belief/attitude about AHT [ 42 87 115 122 ], greater internal locus of control [ 96 ], high confidence in decision [ 123 ], perceived self-efficacy [ 57 81 88 ...…”
Section: Resultsmentioning
confidence: 99%
“…A total of 92 studies identified therapy-related factors affecting adherence to AHT, and drug side effects was a dominant factor in this dimension [ 32 43 48 50 54 57 70 71 73 78 88 90 91 93 97 98 99 102 104 109 114 116 117 120 122 130 131 132 133 134 135 136 137 138 139 140 141 ], followed by the type of AHT and administration of other adjuvant chemotherapy. Most of these were negatively associated with adherence; however, vaginal dryness and hair thinning/loss were positively associated with the continuation of therapy [ 130 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation